Fashioning intellectual property : exhibition, advertising, and the press, 1789-1918 - Richardson, Megan (Cambridge intellectual property and information law ;, 2012)
"Vigorous public debate about intellectual property has a long history. In this assessment of the shifting relationships between the law and the economic, social and cultural sources of creativity and innovation during the long-nineteenth century, Megan Richardson and Julian Thomas examine the 'fashioning' of the law by focusing on emblematic cases, key legislative changes and broader debates. Along the way, the authors highlight how, in 'the age of journalism', the press shaped, and was shaped by, the idea of intellectual property as a protective crucible for improvements in knowledge and progress in the arts and sciences. The engagement in our own time between intellectual property and the creative industries remains volatile and unsettled. As the authors conclude, the fresh opportunities for artistic diversity, expression and communication offered by new media could see the place of intellectual property in the scheme of law being reinvented once again"--